How weak twining lianas adapt to competition with host tree trunks: Case of Merremia boisiana. Issue 4 (1st April 2022) - Hu, Liang; Lin, Yuwei
Abstract: Fierce competition exists between most stem‐twining lianas and the trunks of host trees. However, Merremia boisiana, a vigorous invasive twining liana, never strangles the host tree. Here, we investigated how M. boisiana stems adjust their twining growth to avoid intense competition with host trees, and how hydraulic conductivity is maintained for rapid asexual reproduction. We evaluated the effects of competition on twining M. boisiana stems (Em ) and host tree trunks (Eh ), compared differences in secondary growth between twining and creeping M. boisiana stems, calculated the total number of vessels (Nt ), vessel density (Vmm −2 ), average vessel diameter (VDave ), and percentage of vessels wider than 300 μm in diameter (P300 ) in the secondary xylem, and traced how these parameters change with increasing cross‐sectional area of stem (SA). The results showed that twining M. boisiana stems were competitively weaker, and mean Em (14.3%) was 21 times greater than that of Eh (0.7%). Secondary growth along the normal direction of the contact surface was significantly inhibited in stems twining on host trees. The lateral secondary growth of these stems was active, forming secondary vascular rings and/or arcs with abundant large vessels. Secondary growth in the central vascular cylinder was also significantly limited in extremely flat twining stems. Nt was positively and linearly correlated with SA. Vmm −2 and VDave fluctuated greatly in younger stems and tended to be stable in older stems. Nt and Vmm −2 did not significantly differ between twining and creeping stems, while VDave and P300 were both higher in twining stems compared to creeping stems of the same size. In conclusion, well‐developed lateral anomalous secondary growth prevents twining M. boisiana stems from fiercely competing with their host trees, while stable vessel density and wider, newly formed, vessels ensured sufficient hydraulic conductivity for the rapid asexual reproduction of twining M. boisiana stems. Abstract : The total number of vessels in secondary xylem (Nt ) was positively and linearly correlated with cross‐sectional area of stem. Vessel density (Vmm ‐2 ), average vessel diameter (VDave ), and percentage of vessels wider than 300 μm in diameter (P300 ) fluctuated greatly in younger stems and tended to be stable in older stems.